Association between low back pain and various everyday performances: Activities of daily living, ability to work and sexual function - Grabovac, Igor (Wien Klin Wochenschr, 2019)
Low back pain (LBP) is a widely prevalent chronic pain disorder associated with a high burden on individuals and society. In the subjective perception of patients with LBP, probably the most important health outcomes associated with LBP are those that effect everyday performance. Such outcomes include reduction in activities of daily living (ADL), in work ability (WA), and in sexual function. This narrative review aimed to (1) examine the association between LBP and the three mentioned outcomes of everyday performance, (2) to explain possible mediating factors promoting these associations, and (3) to discuss possible implications for treatment and rehabilitation. Studies have shown that LBP can generate anxiety of movement leading to movement avoidance (fear-avoidance beliefs), which may lead to deconditioning and further increasing problems with ADL, WA and decreasing sexual function. Furthermore, common mental disorders, such as depression, anxiety, and stress-related disorders, which also often co-occur with LBP can lead to adverse effects on everyday performance and vice versa, can be the consequence of such problems and aggravate LBP. Although there is no universally accepted treatment modality that fits every patient with LBP, physical training, comprehensive patient education, and workplace or home modifications have been shown to be able to interrupt the mutual influence between LBP and the described mediating factors, and have a beneficial effect on ADL, WA, and sexual function. For this, a multidisciplinary approach is necessary which includes multiprofessional care teams, participation of the patients, and involvement of different settings, such as workplace, home, and physical training facilities.